Development of a Model Updating Technique Using Soft Computing - Yadav, Yogesh; Saud, Ishwor Singh (Journal of Advanced College of Engineering and Management, 2022)
The structural models, do not necessarily predict the measured data sufficiently accurately. Because of this, there is a need for these models to be updated to better reflect the measured data. This paper introduces computational intelligence techniques to update finite element models. The model updating is formulated as a constrained optimization problem and solved using a recently developed meta-heuristic algorithm called Artificial Bee Colony (ABC) algorithm. A MATLAB code is developed using the model-updating formulations presented in this paper. Numerical simulation studies are carried out by solving for the proposed model updating technique by using pseudo-experimental data of an 8storey framed structure and also the experimental data of ASCE three storey benchmark structure. Studies presented in this paper clearly indicate the effectiveness of the proposed computational intelligence-based model updating technique.